2007
DOI: 10.1152/ajpendo.00106.2007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic challenges reveal impaired fatty acid metabolism and translocation of FAT/CD36 but not FABPpm in obese Zucker rat muscle

Abstract: Han X-X, Chabowski A, Tandon NN, Calles-Escandon J, Glatz JF, Luiken JJ, Bonen A. Metabolic challenges reveal impaired fatty acid metabolism and translocation of FAT/CD36 but not FABPpm in obese Zucker rat muscle. Am J Physiol Endocrinol Metab 293: E566-E575, 2007. First published May 22, 2007; doi:10.1152/ajpendo.00106.2007.-We examined, in muscle of lean and obese Zucker rats, basal, insulin-induced, and contractioninduced fatty acid transporter translocation and fatty acid uptake, esterification, and oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
80
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 57 publications
13
80
1
Order By: Relevance
“…However, this literature is based on in vitro measurements that are optimised to determine the capacity of mitochondrial function and therefore may not represent the in vivo oxidative flux. In support of this, in the obese Zucker rat, despite increased mitochondrial density as shown here and elsewhere [9,38], and despite increased in vitro mitochondrial function [9], we (present study) and others [41] found that rates of total muscle fatty acid oxidation were decreased, while, as found here, rates of triacylglycerol esterification were increased. It should be noted that the notion that fatty acid oxidation is reduced in obese Zucker rats [15,42,43] is controversial.…”
Section: Mitochondrial Subcellular Alterations and Fatty Acid Metabolismsupporting
confidence: 92%
See 2 more Smart Citations
“…However, this literature is based on in vitro measurements that are optimised to determine the capacity of mitochondrial function and therefore may not represent the in vivo oxidative flux. In support of this, in the obese Zucker rat, despite increased mitochondrial density as shown here and elsewhere [9,38], and despite increased in vitro mitochondrial function [9], we (present study) and others [41] found that rates of total muscle fatty acid oxidation were decreased, while, as found here, rates of triacylglycerol esterification were increased. It should be noted that the notion that fatty acid oxidation is reduced in obese Zucker rats [15,42,43] is controversial.…”
Section: Mitochondrial Subcellular Alterations and Fatty Acid Metabolismsupporting
confidence: 92%
“…The increase in subsarcolemmal mitochondrial density and fatty acid oxidation may represent compensatory mechanisms designed to prevent lipid droplet accumulation in the subsarcolemmal region. Therefore, reduced mitochondrial fatty acid oxidation apparently cannot account for the observed intramuscular lipid accumulation, a notion that is consistent with contemporary mitochondrial literature [37][38][39][40][41]. However, this literature is based on in vitro measurements that are optimised to determine the capacity of mitochondrial function and therefore may not represent the in vivo oxidative flux.…”
Section: Mitochondrial Subcellular Alterations and Fatty Acid Metabolismsupporting
confidence: 54%
See 1 more Smart Citation
“…Muscle Triacylglycerol-Concentrations of intramuscular triacylglycerol were determined using thin layer chromatography, as outlined elsewhere (38). Briefly, muscle (50 mg) was homogenized (Polytron, Kinematica AG, Brinkmann, LittauLucerne, Switzerland) in 2 ml of 1:1 chloroform/methanol on ice.…”
Section: Muscle Triacylglycerol Content Mitochondrial Isolation Andmentioning
confidence: 99%
“…1). Some fatty acid transporters have now also been implicated in the dysregulation of fatty acid metabolism in heart and skeletal muscle in models of insulin resistance and type 1 and 2 diabetes, including FAT/CD36 (5-9), FATP1 (10,11), and possibly FATP4 (11,12) but not FABPpm (5)(6)(7). Thus, in recent years, it has become widely accepted that (a) long chain fatty acids traverse the plasma membrane via a protein-mediated mechanism and (b) some of the fatty acid transporters are central to the dysregulation in skeletal muscle fatty acid metabolism in obesity and type 2 diabetes.…”
mentioning
confidence: 99%